Livelihood Adaptation Approaches in Forest: A Case Study of Forest Villagers in Alipurduar District, West Bengal (International Journal of Food and Nutritional Sciences, 2023)
There is a description of various adaptation skills of sampled forest villagers. The physical site and location of forest villages has a profound direct or indirect influence on the way of life of villagers which have to adapt according to the indigenous technique capacities. So the manner, customs and behaviour related to forest environment i.e. land use, food habit, fuel used, plants used as traditional medicine, source of water facilities, house types and forest based other activities have been expressed to make the idea of lifestyle adaptation by forest villagers in Alipurduar district area. The study notified that land use pattern, food habit, fuel used, house type, water storage facilities, type of NTFPs collection of high altitude area is differ from low-lying area households. It is also depicted that although villagers adapted to natural environment but physical characteristics are the principal causes for variation in the socio-economic behabiour of high altitude and low lying area households of forest villages of this locality.